Spatial and temporal salinity distribution in the water column of the estuarine sector of the Térraba Sierpe National Wetland, Costa Rica. - Picado Barboza, Jorge (2015)
The analysis of salinity data collected during three campaigns of monitoring (2002-2004, 2005-2008 and 2011-2012) in the estuarine sector of Térraba Sierpe National Wetlands (HNTS) was performed. The information collected allows to separate a northern zone with a strong influence of the Río Grande de Térraba, which during the period of low flow (December-April) shows characteristics of a partially mixed estuary, while it resembles a salt-wedge estuary during intermediate and high flows rates (May-November). A central area with greater marine influence features a vertically homogeneous or well mixed estuary, while the south of the estuary has a balanced (intermediate) condition, through the contributions of the Sierpe river and the tidal regime, which confers characteristics of a partially mixed estuary. The statistical analysis model confirms variations in the salinity values in relation to tides, time of year (season) and the distance along a longitudinal profile of 24km away from the town of Ciudad Cortés to the sea opening at Coronado mouth (F1,47=2.5, p<0.001). The first 7km downstream from Ciudad Cortes have a very well-defined fluvial condition with salinities below 1psu, in the sector of Viuda island, located 8km towards the sea, there is a range of variation in salinity values higher than 5psu; a final section that starts 14km towards the Coronado mouth shows a gradual increase in the salinity values up to 30psu reflecting a greater influence of the tides. The eventual development of the El Diquis hydroelectric project could cause an increase in the contribution of freshwater between an 82-66% of the minimum and maximum average flow values over the northern part of the estuarine sector of the HNTS during the low flow periods, which would create similar conditions to those recorded during the intermediate flow rates. The provided analysis constitutes a first approach to the understanding of the estuarine dynamics of the HNTS. Analysis and monitoring of the relationships between the physical, chemical and biological aspects are essential for future discern between possible sources of changes in the estuarine sector of the HNTS and must be considered to be a firm commitment by the institutions involved in the management and conservation of this ecosystem.